2016
DOI: 10.17557/tjfc.18296
|View full text |Cite
|
Sign up to set email alerts
|

FEED VALUE OF BLUE PANIC (Panicum antidotale retz.) GRASS AT DIFFERENT GROWTH STAGES AND UNDER VARYING LEVELS OF HUMIC ACID IN SALINE CONDITIONS

Abstract: This study underscored an underexploited crop, blue panic grass as a potential crop for hot and saline regions. It investigated feed value of the crop at two growth stages, before flowering (BF) and after flowering (AF), and under different levels of humic acid application (HA, at 0, 15, 30, 45, 60, 75, and 90 kg ha −1). Significant (P < 0.05) effects of different growth stages, HA while non-significant effect of their interactions were observed for various parameters. Low dry matter (DM) was recorded for cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Silage made at once cut during season had greater NDF and ADF concentrations than the other cutting treatments. Many research workers (Geren et al, 2014;Daur, 2016;Atis et al, 2019) emphasized that hay or silage made by wizened grass is not a good option to feed livestock due to the lower quality. On the other side, some researchers emphasized that if managed well (plant age, cutting height, etc.)…”
Section: Ndf and Adf Contentmentioning
confidence: 99%
“…Silage made at once cut during season had greater NDF and ADF concentrations than the other cutting treatments. Many research workers (Geren et al, 2014;Daur, 2016;Atis et al, 2019) emphasized that hay or silage made by wizened grass is not a good option to feed livestock due to the lower quality. On the other side, some researchers emphasized that if managed well (plant age, cutting height, etc.)…”
Section: Ndf and Adf Contentmentioning
confidence: 99%
“…The same trends were also found for other tested grasses such as buffelgrass, bell Rhodes grass and Kleberg bluestem. ( Daur, 2016 ) also found that nitrogen content in blue panicgrass shoots declined by 7% when harvested after flowering compared to the early stage before flowering. The same trend was found by ( Mirza et al., 2002 ) where nitrogen content in blue panicgrass and other tested grass shoots declined with the advancement of growth stages.…”
Section: Discussionmentioning
confidence: 90%
“…(2015) , who reported that NDF and ADF contents increased by 6% for 30 days compared to 15 days. Furthermore, Daur (2016) reported that NDF and ADF content in blue panicgrass was about 59 and 31% before flowering (35 days) and increased to 72 and 38%, respectively, after flowering (45 days). A negative relationship between ash and crude protein, with crude fiber, NDF, and ADF, was reported in several other studies.…”
Section: Discussionmentioning
confidence: 99%